Upaya Meningkatkan Kemampuan Berhitung Melalui Media Pembelajaran Papan Jurang Pada Siswa Kelas II SD YPK Bethania Mariadei - Sahara, Desy Putri; Katulung, Marlin; Nurhartina, Andi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Based on the results of interviews conducted with grade 2 teachers of YPK Bethania Mariadei Elementary School, it was obtained that students still had difficulty in understanding the material on addition and subtraction operations (borrowing and without borrowing). After conducting initial observations to measure students' initial abilities, the following information was obtained: 1) 2 students out of 21 students with a percentage of 9.5% obtained scores above or reaching the KKM, 2) 19 students out of 21 students with a percentage of 90.5% had not obtained scores reaching the KKM. As for the minimum completion score in Mathematics, it is 60 with a success indicator of ≥ 75%. The purpose of this study is to improve students' addition and subtraction arithmetic skills through the use of the cliff board learning media (addition and subtraction). This study uses a classroom action research method. Data collection was taken using a learning outcome test on the ability to count addition and subtraction arithmetic and observations for teacher and student activities using qualitative and quantitative analysis. The results achieved after implementing the ravine board media (addition and subtraction) are that in learning activities it was found that there was an increase in student abilities above the KKM in cycle I reaching 42.9% while in cycle II it reached 86%. So it can be concluded that the application of the ravine board learning media (addition and subtraction) can improve the ability to calculate addition and subtraction in grade 2 students of YPK Bethania Mariadei Elementary School